Morphological and phylogenetic reassessment of Sclerococcum simplex from China - Thiyagaraja, Vinodhini; Ertz, Damien; Hyde, Kevin D.; Karunarathna, Samantha C.; To-Anun, Chaiwat; Cheewangkoon, Ratchadawan (Phytotaxa, 2022)
Sclerococcum is a species rich lichenicolous genus in Ascomycota. However, many species of Sclerococcum have been described based only on morphology. This study provides sequences for the large-subunit ribosomal RNA (LSU), internal transcribed spacer (ITS) and mitochondrial small-subunit ribosomal RNA (mtSSU) for the first time for Sclerococcum simplex, and the first geographical record of the genus from China. Phylogenetic analyses confirmed that S. simplex clustered within Sclerococcum sensu stricto while the genus was recovered as paraphyletic in Dactylosporaceae. Our asexual specimen of Sclerococcum simplex was collected on a corticolous Pertusaria thallus. The taxonomic affinity of Sclerococcum simplex is investigated based on phylogenetic and morphological evidence.